Integrasi Tata Letak Pohon dan Penilaian Risiko dalam Perancangan Koridor Jalan di Kota Bogor - Fariz Harindra Syam; Nike Dyah Permata; Adlia Vidya Rahmandari (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2026)
Urban street trees provide essential ecosystem services, including thermal regulation, carbon sequestration, and aesthetic enhancement. However, poorly maintained or structurally compromised trees pose significant safety risks, such as branch failure or complete collapse. This study explores the integration of tree risk assessment into the design of urban street corridors to improve safety and sustainability. Field observations were conducted along Salak street and Pangrango street in Bogor, Indonesia, using the Visual Tree Assessment (VTA) method and the International Society of Arboriculture (ISA) Basic Tree Risk Assessment protocol. Seven sample trees were evaluated for structural defects, site conditions, and potential targets. Results indicate that trees located along road edges exhibit higher risk levels compared to those in open spaces, primarily due to restricted root zones, codominant stems, and excessive crown size. Approximately 70% of roadside trees fall within medium to high-risk categories, with imminent failure observed in cases of severe trunk inclination and root damage. Recommended mitigation strategies include crown pruning to reduce load, removal of hazardous codominant stems, relocation of nearby infrastructure, and routine monitoring at monthly intervals. Integrating tree risk management into corridor planning ensures that urban green infrastructure remains both functional and safe, supporting long-term resilience and public safety